Prediction of the Tuban Regency Open Unemployment Rate in 2022 with the Backpropagation Method - Evi Septya Putri; Abdulloh Hamid; Dian C. Rini Novitasari (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
The Open Unemployment Rate is the number of unemployed from the total labor force in an area or region in the form of a percentage. In Tuban Regency, unemployment has experienced a very significant increase from 2019 to 2020. Therefore, it is necessary to make predictions in 2021 and 2022 to find out the description of the Open Unemployment Rate in that year so that actions can be taken by the government to deal with this. By using the Backpropagation method, this study obtained predictions that in 2021 it will be 4.58% of the total workforce in Tuban Regency in 2021 and in 2022 the open unemployment rate will be 4.7% of the total workforce in Tuban Regency in 2022, with network architecture 2-70-1-1, the learning rate used is 0.1 and the MAPE value is 8.363%. The test was stopped at the 276th epoch. At the time of testing between the output and the target there was a correlation (R) of 0.993 where the best result was 1.